Identification of Indian pathogenic races of fusarium oxysporum f. sp ciceris with gene specific, ITS and random markers - Gurjar, Gayatri; Barve, Maneesha; Giri, Ashok P.; Gupta, Vidya (Mycologia, 2009)
In this study we demonstrate the synergistic use of gene-specific markers, ITS-RFLP, ISSR and AFLP for distinguishing Indian F. oxysporum f. sp. ciceris races. We also report for the first time that F. oxysporum f. sp. ciceris race 3, a wilt pathogen of chickpea in India, is actually E proliferatum based on phylogenetic analysis with EF-1 alpha sequence data. E oxysporum f. sp. ciceris races 1, 2 and 4 were easily distinguished from ``race 3'' (F. proliferatum) by PCR amplification with oligonucleotides designed from conserved regions of Hop78 transposon (Hop 78), cutinase (Cut), desaturase (Dst). F oxysporum f. sp. ciceris race 4 was distinguished with the xylanase 3 (xyl3) gene by absence of amplification product only in this race. The Xyl3 amplified-DNA fragment isolated and sequenced from E oxysporum f. sp. ciceris race I was similar to the F-xylanase (Xyl3) gene of E oxysporum f. sp. lycopersici. A TELD motif, which is characteristic of the F-xylanases family, was detected within the deduced amino acid sequence of F. oxysporum f. sp. ciceris. Similarly the F oxysporum f. sp. ciceris Hop78 DNA fragment, which identified ``race 3'' (E proliferatum), was homologous to the Hop78 transposon of E oxysporum f. sp. melonis, including the 100 amino acid conserved domain and the characteristic CCHC motif. The internal transcribed spacer region-restriction fragment length polymorphism (ITS-RFLP) approach along with intersimple sequence repeat (ISSR) method also differentiated ``race 3'' (F. proliferatum). Races 1 and 2 were identified by unique AFLP patterns. Sequence characterization of race-specific AFLP products revealed significant homologies of these sequences with metabolically important genes.
Keywords: AFLP; F. oxysporum f. sp ciceris races; gene specific amplification; ISSR; ITS-RFLP; race delineation; sequence characterization; translation elongation factor (EF-1 alpha)